Fistula formation in hepatic cystic echinococcosis: clinical impact, predictors, and outcomes from a 27-year cohort - Inmaculada Izquierdo Pérez; Amparo López-Bernus; Angela Romero Alegría; Montserrat Alonso-Sardón; Beatriz Rodriguez Alonso; Hugo Almeida; Josué Pendones; Javier Pardo-Lledías; Moncef Belhassen-García (Transactions of The Royal Society of Tropical Medicine and Hygiene, 2026)
Abstract Background Hepatic cystic echinococcosis (HCE) is a chronic parasitic disease with a highly variable clinical course. Fistula formation represents one of its most clinically relevant complications, yet its determinants and prognostic impact remain incompletely defined. Methods We conducted a retrospective observational cohort study including patients with cystic echinococcosis managed at a tertiary referral centre between 1998 and 2025. Patients with hepatic involvement were classified according to the presence or absence of fistula formation. Clinical, laboratory, radiological, treatment and outcome variables were compared. Results Among 539 patients with HCE, 87 (16.1%) developed fistula formation. Cystobiliary fistula was the predominant subtype (n=80), followed by transdiaphragmatic fistulas. Patients with fistulas were younger and more frequently symptomatic, with higher rates of complications. Fistula formation was independently associated with active cyst stages (CE1–CE3), cyst diameter >7 cm and eosinophilia. Despite increased clinical complexity, no significant differences were observed between patients with and without fistula in recurrence, all-cause mortality, CE-related mortality or length of hospital stay. Conclusions Fistula formation in HCE identifies a subgroup of patients with larger and biologically active cysts, reflecting increased disease complexity rather than worse prognosis. When managed in specialised centres, fistulization does not appear to adversely affect long-term outcomes. Early identification of high-risk cysts may support targeted monitoring and timely intervention, particularly in endemic settings.